The Role of Intestinal Microbiota in Colorectal Cancer - Lingli Ren; Lingli Ren; Juan Ye; Juan Ye; Bing Zhao; Bing Zhao; Jinbing Sun; Peng Cao; Peng Cao; Yang Yang; Yang Yang; Yang Yang; et al. (Frontiers Media S.A., 2021)
Colorectal cancer is a multifactorial disease involving genetic, environmental, and lifestyle risk factors. Intestinal microbiota plays an important role in the occurrence and development of colorectal cancer. Studies have shown that the behavior of intestinal microbiota can lead to pathological changes in the host intestine, which can be divided into epigenetic changes and carcinogenic changes at the gene level, and ultimately promote the formation and development of colorectal cancer. Intestinal microbiota is mainly distributed in the intestinal epithelium, which is composed of a large number of microorganisms interacting with the host intestinal cells. It can affect the immune-inflammation and metabolism of the gastrointestinal tract, and may be used as a biomarker for disease diagnosis. Regulation of gut microbiota is a promising strategy for the prevention and treatment of colorectal cancer. This article reviews the role of intestinal microbiota in the development of colorectal cancer, including the related mechanisms of intestinal microbiota promoting colorectal cancer, the use of intestinal microbiota in the diagnosis of colorectal cancer, and the regulation of intestinal microbiota in the prevention or treatment of colorectal cancer.